Stock assessment of the needle cuttlefish Sepia aculeata Orbigny - Rao, K Satyanarayana; Srinath, M; Meiyappan, M M; Nair, K Prabhakaran; Sarvesan, R; Rao, G Syda; Natarajan, P; Vidyasagar, Kuber; Sundaram, K S; Lipton, A P; Radhakrishnan, G; Narasimham, K A; et al. (Indian Journal of Fisheries, 2011)
The needle cuttlefish Sepia aculeata, along with Sepia pharaaonis, forms the mainstay of India’s cuttlefish resource. A study of the present status of its fishery liased on the data collected at different centres on both the coasts of India for 1979-1989 indicates that the production has Increased many times in recent years, with Maharashtra alone accounting for about 60% of the total production (10 7241 in 1989) of this cuttlefish. Over 88% of the total production was taken in trawl net as by-catch. The third quarter of the year is the most productive and the first quarter the least on the east coast; on the west coast the fourth quarter is the best season, with the niinimun catch during the third quarter (July- September). The natural mortality rates calculated based on different M/K values (1.5,2 and 2.5) range from 1.33 to 2.25 in both males and females on the east coast; on the west coast they are 1.65-2.75 for males and 1.5-2.S for females. The maximum fishing mortality is at the size of 90 mm for males and 150 mm for females on the east coast, and at 150 mm for males and 170 for females on the west coast. The standing stock estimates at all levels of M/K are higher for females than for males on both the coasts. The MSY and mean biotnass estimates indicate that the present catches are optimal on the east coast but on the west coast there Is considerable scope for increasing production